Effect of hyperbranched poly(butyl methacrylate) on polymer diffusion in poly(butyl acrylate-co-methyl methacrylate) latex films - Liu, Yuanqin (2010)
Latex paint formulations normally contain volatile organic compounds (VOCs) to lower the modulus of the latex polymer and to enhance the rate of its diffusion in latex films. Here we show that hyperbranched poly(butyl methacrylate) (HB-PBMA) not only is miscible with poly(butyl acrylate-co-methyl methacrylate) [P(BA-MMA)] copolymers over a range of BA/MMA compositions but also acts as a diffusion promoter. At similar volume fractions (≤0.1), it is as effective at promoting P(BA-MMA) polymer diffusion as 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate (Texanol, TPM), a classic coalescing aid. Unlike TPM, it does not cause a large decrease in the glass transition temperature of the polymer, and it has relatively little effect on the modulus of the polymer. Small molecule additives commonly lead to a reduction of useful mechanical properties of a polymer, such as tensile strength and toughness. Tensile tests show that P(BA-MMA) latex films containing HB-PBMA have better mechanical properties than the corresponding films containing TPM. Thus, this hyperbranched polymer represents a new kind of nonvolatile additive for latex that can promote the rate of polymer diffusion in latex films without significantly disrupting the desirable mechanical properties of the film.